2021
DOI: 10.1021/acs.jmedchem.1c01353
|View full text |Cite
|
Sign up to set email alerts
|

Structure Activity Relationships for a Series of Eticlopride-Based Dopamine D2/D3 Receptor Bitopic Ligands

Abstract: The crystal structure of the dopamine D3 receptor (D3R) in complex with eticlopride inspired the design of bitopic ligands that explored (1) N-alkylation of the eticlopride’s pyrrolidine ring, (2) shifting of the position of the pyrrolidine nitrogen, (3) expansion of the pyrrolidine ring system, and (4) incorporation of O-alkylations at the 4-position. Structure activity relationships (SAR) revealed that moving the N- or expanding the pyrrolidine ring was detrimental to D2R/D3R binding affinities. Small pyrrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…In the following parts, we designated the D 2 R modulators that do not structurally fit into the 1,4‐DACA group or did not contain the necessary data (top‐ranked candidate evaluated in vivo as a potential drug for management of schizophrenia, PD, depression or anxiety, or proved to be selective D 2 R, biased or bivalent ligand) so we discussed them in detail in section “2.5 1,4‐Disubstituted aromatic/heteroaromatic cyclic amine derivatives affecting dopamine D 2 Rs—their structure, function, and pharmacological profiles.” These analogs fall within the more general pharmacophore of D 2 R and even D 3 R, as shown in Figure 64. This pharmacophore consists of the so‐called primary pharmacophore, which is further composed of aromatic/heteroaromatic head and amine moieties, a central linker, and a so‐called secondary pharmacophore 490,527,775–777 . The primary pharmacophore binds to the orthosteric binding site, whereas the secondary pharmacophore binds to the allosteric (secondary) binding site 776,777 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following parts, we designated the D 2 R modulators that do not structurally fit into the 1,4‐DACA group or did not contain the necessary data (top‐ranked candidate evaluated in vivo as a potential drug for management of schizophrenia, PD, depression or anxiety, or proved to be selective D 2 R, biased or bivalent ligand) so we discussed them in detail in section “2.5 1,4‐Disubstituted aromatic/heteroaromatic cyclic amine derivatives affecting dopamine D 2 Rs—their structure, function, and pharmacological profiles.” These analogs fall within the more general pharmacophore of D 2 R and even D 3 R, as shown in Figure 64. This pharmacophore consists of the so‐called primary pharmacophore, which is further composed of aromatic/heteroaromatic head and amine moieties, a central linker, and a so‐called secondary pharmacophore 490,527,775–777 . The primary pharmacophore binds to the orthosteric binding site, whereas the secondary pharmacophore binds to the allosteric (secondary) binding site 776,777 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above‐mentioned 1,4‐DACA, some specific fragments were used as primary pharmacophores, namely 7‐piperazinyl and 7‐piperidinyl‐3,4‐dihydroquinazolin‐2(1 H )‐one, 778 5‐piperidinyl and 5‐piperazinyl‐1 H ‐benzo[ d ]midazole‐2(3 H )‐one, 779 4‐(1‐benzimidazolinone)piperidine, 780 sumanirole, 489,490,776,777 tranylcypromine, 472 pramipexole, 469 2‐phenylcyclopropylmethylamine, 527 eticlopride, 479,775 1,2,3,4‐tetrahydro‐3‐quinolinamine, 776 tetracyclic, 781 tetrahydroisoquinoline, 480,498,594,595,600,782–787 or 1,3‐disubstituted morpholine 438,474,490,493,788 . Various aliphatic, 477,515,516,602,789–793 bicyclic 794–797 or spirocyclic 798 amines have also been used for amine moiety.…”
Section: Discussionmentioning
confidence: 99%
“…In BRET assays, these compounds exhibited antagonist or very weak partial agonist behaviour. Docking studies revealed that the SPs of the O-alkylated analogues form aromatic stacking interactions with conserved residues His6.55 and Tyr7.35 both in the D 2 and D 3 receptors, while the SPs of the N-alkylated derivatives extend towards the extracellular site that is less conserved (Shaik et al, 2021). N-phenylpiperazine analogues were used extensively for constructing bitopic ligands against dopamine receptors.…”
Section: Receptor and Subtype Selectivitymentioning
confidence: 99%
“…[58][59][60][61][62][63] Among many other examples, a large number of D3-R agonists were derived from pramipexole, 64 with high-affinity D3R agonists with pKi values as high as 8.0. 65 Other authors attempted to find selectivity toward one or the other of D2 and D3 receptors with new ligands derived from eticlopride 66 or cariprazine. 67 The recent availability of crystal structures for the D2 or D3 dopamine receptors [68][69][70] will also help developing new approaches for specific ligands, either agonists or antagonists.…”
Section: Conclusive Remarksmentioning
confidence: 99%